Transcriptional memory in the Drosophila embryo - Ferraro, Teresa (Curr Biol, 2015)
Transmission of active transcriptional states from mother to daughter cells has the potential to foster precision in the gene expression programs underlying development. Such transcriptional memory has been specifically proposed to promote rapid reactivation of complex gene expression profiles following successive mitoses in Drosophila development [1]. By monitoring transcription in living Drosophila embryos, we provide the first evidence for transcriptional memory in animal development. We specifically monitored the activities of stochastically expressed transgenes in order to distinguish active and inactive mother cells and the behaviors of their daughter nuclei following mitosis. Quantitative analyses reveal that there is a 4-fold higher probability for rapid reactivation following mitosis when the mother experienced transcription. Moreover, memory nuclei activate transcription twice as fast as neighboring inactive mothers, thus leading to augmented levels of gene expression. We propose that transcriptional memory is a mechanism of precision, which helps coordinate gene activity during embryogenesis.